Alkenes - Davarnejad, Reza; Sajjadi, Baharak (IntechOpen, 2018)
In organic chemistry, Alkenes, also known as olefins, are the unsaturated hydrocarbons with the general formula of CnH2n that contains one or more carbon-carbon double bonds in their chemical structures (RC=CR'). The presence of this double bond allows alkenes to react in ways that alkanes cannot. Hence, alkenes find many diverse applications in industry. These compounds are widely used as initial materials in the synthesis of alcohols, plastics, lacquers, detergents, and fuels. The current book includes all knowledge and novel data according to the structure of alkenes, their novel synthesis methods, and their applications. In addition, manufacture, properties, and the use of polyalkenes are the other important topics that are covered in this book. These data are collected by the efforts and contributions of many authors and scientists from all over the globe, and all of us are ready to further improve the contents of this book as per the readers' comments.